Investigation of the effect of cathode stoichiometry of proton exchange membrane fuel cell using localized electrochemical impedance spectroscopy based on print circuit board. (15th March 2019) - Liu, Dengcheng; Lin, Rui; Feng, Bowen; Yang, Zhen
Abstract: Proton Exchange Membrane Fuel Cell can have a large active area, and the working condition in different areas can be entirely different. Localized electrochemical impedance spectroscopy can directly observe the proton exchange membrane fuel cell internal reaction conditions. In this work, localized electrochemical impedance spectroscopy test system based on print circuit board is implemented in a 50 cm 2 multi-channel serpentine flow fields. The localized electrochemical impedance spectroscopy performances of different segments with different cathode stoichiometry (1.8, 2.3 and 2.8) at different current density (100 mA cm −2, 500 mA cm −2 and 900 mA cm −2 ) are studied. The result demonstrates that the fuel cell may suffer from local drying and flooding at the same time. To make full use of the potential of a fuel cell, a suitable cathode stoichiometry should be identified to control the drying of the inlet and the flooding of the outlet at the same time. It is shown that a cathode stoichiometry of 2.3 is close to the optimum cathode stoichiometry to keep the fuel cell in good consistency without gas waste. Besides, a current density distribution measurement is performed to verify the conclusions of this work. Graphical abstract: Image 1 Highlights: Localized electrochemical impedance spectroscopy is analysed for stoichiometry study. Fuel cell might suffer from local drying and flooding at the same time. The cathode outlet may have flooding problem even at medium current density. Increasing cathode stoichiometry may dry the membrane near the cathode inlet. Cathode stoichiometry of 2.3 can make better use of every part's potential.